Intensity of the Reader’s Voice in the Reading Aloud of Fiction: Effects of the Character’s Gender - Stolarski, Łukasz (Studia Anglica Posnaniensia, 2017)
Contrary to what had been expected, a statistical analysis of the results revealed no effects of the character’s gender on any of the response variables. However, conclusions concerning secondary aims were more definitive. A general trend to decrease the SD of SPL in dialogues in comparison to the rest of the text in a novel was observed. This tendency is independent of any of the factors included in the study. It was also observed that male American readers tend to lower their voice intensity when reading dialogues. All these findings may be applied in developing text to speech software.